Perbandingan Pengaplikasian Teknik Koreksi Alis Menggunakan Lem Bulu Mata dan Eyebrow Pencil terhadap Hasil Koreksi Bentuk Alis Tebal pada Tata Rias Pengantin Koto Gadang - Fidella Eriza Putri; Mitra Lusiana (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Eyebrow makeup is an important element in facial makeup, especially in Koto Gadang bridal makeup which highlights the beauty and harmony of the face as a whole. Thick eyebrows are often a challenge because they are difficult to shape and groom without shaving. This study aims to compare the results of correction of thick eyebrow shape using two techniques, namely eyelash glue and eyebrow pencil, in the context of Koto Gadang's bridal makeup. This study uses an experimental method with a quantitative approach. The sample consisted of six female students of Padang State University who were divided into two groups: three people using the eyelash glue technique and three people using eyebrow pencil. Data were collected through observations, documentation, and research instruments, and then analyzed using normality, homogeneity, and independent sample t-test. The results of the study show that there is a significant difference between the two techniques. The use of eyelash glue resulted in an ideal eyebrow shape of 81%, flatness 66.7%, adhesion 61.9%, and aesthetics 66.7%. Meanwhile, the eyebrow pencil technique obtained scores of 52.4%, 71.4%, 61.9%, and 76.2%, respectively. The statistical test showed a p<0.05 value on all aspects tested, indicating a significant difference. The conclusion of this study suggests the use of eyelash glue as a thick eyebrow correction technique because it provides durability and more even results than eyebrow pencils.